2019
DOI: 10.1002/celc.201901770
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Hard Carbon on Nickel Foam as Free‐Standing Anodes for High‐Performance Sodium‐Ion Batteries

Abstract: Nitrogen‐doped hard carbon on Ni foam (NC/NF) with numerous active sites, expanded interlayer distance (0.49 nm), and highly ordered pseudo‐graphic structure is synthesized by a melamine‐assisted hydrothermal pretreatment and subsequent pyrolysis procedure. The high content configurations of pyrrolic‐nitrogen and pyridinic‐nitrogen in NC/NF could provide abundant active sites and defects for efficient Na+ adsorption/desorption and improved transport kinetics. The obvious flocculent structures on carbon surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…36,37 Contrast of the initial and subsequent discharge profiles indicated the irreversible capacity loss of the N-V 2 O 3 , N-VO 0.9 and VN electrodes, associated with the formation of the SEI layer and the decomposition process on the surface of oxides and nitrides. [37][38][39] It is observed that the charge-discharge curves of the N-V 2 O 3 electrode display gently slope shapes, in accordance with its CV curves and further revealing the capacitive storage behavior. In the following cycles, the charge-discharge profiles are almost overlapped at different current densities, further confirming that the N-V 2 O 3 , N-VO 0.9 and VN electrodes exhibit cycling stability and Li + -storage reversibility (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Contrast of the initial and subsequent discharge profiles indicated the irreversible capacity loss of the N-V 2 O 3 , N-VO 0.9 and VN electrodes, associated with the formation of the SEI layer and the decomposition process on the surface of oxides and nitrides. [37][38][39] It is observed that the charge-discharge curves of the N-V 2 O 3 electrode display gently slope shapes, in accordance with its CV curves and further revealing the capacitive storage behavior. In the following cycles, the charge-discharge profiles are almost overlapped at different current densities, further confirming that the N-V 2 O 3 , N-VO 0.9 and VN electrodes exhibit cycling stability and Li + -storage reversibility (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3d–f deliver the sloping voltage profiles with no obvious plateaus between 0.01 and 3.0 V. Additionally, the sloped region corresponds to the Li + adsorption storage in a wide range at a high potential and the plateau region corresponds to embedded storage lithium at a lower potential, which are corresponding to the weak dumps of the CV curves. 36,37 Contrast of the initial and subsequent discharge profiles indicated the irreversible capacity loss of the N-V 2 O 3 , N-VO 0.9 and VN electrodes, associated with the formation of the SEI layer and the decomposition process on the surface of oxides and nitrides. 37–39 It is observed that the charge–discharge curves of the N-V 2 O 3 electrode display gently slope shapes, in accordance with its CV curves and further revealing the capacitive storage behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, researchers have found that the local graphite microcrystalline structure can be regulated by introducing metal ions and heteroatoms (N, C, etc. ), [59][60][61] which can effectively improve electron transport and ions diffusion during electrochemical reactions. As shown in Figure 3a, Wu et al [62] doped natural K þ into hard carbon, resulting in the (002) diffraction peak shifting to lower angle of in-XRD (Figure 3c), which effectively enlarged the interlayer spacing (0.4 nm) and improved the cycle performance of the battery (Figure 3b).…”
Section: Crystallitesmentioning
confidence: 99%
“…Both pyrrolic and pyridinic N, with their extra pair of electrons, exhibit high chemical reactivity as electron-rich donors, facilitating the de-solvation process of lithium ions. 24,44,45 Conversely, graphitic nitrogen is unreactive with lithium ions due to its provision of two single electrons in two orbitals. 45 Lithium symmetric cell analysis.…”
Section: Sample Preparation P-ccmentioning
confidence: 99%